United Nations Handbook - Shelton, Ann (Service by Context public policy Communications/ Wellngton, 2009)
Now in its 47th year of publication, the United Nations Handbook remains the only comprehensive printed guide to the United Nations system and its functioning. The handbook summarizes all United Nations organizations and provides essential information on their objectives, structures, and membership. This unique publication is widely used by those working in the United Nations system, from diplomats on the negotiating floor to international civil servants and non-governmental organizations. It is also an invaluable resource for journalists, businesses, libraries, academics, schools, and members of the public.